PERANCANGAN APLIKASI MANAJEMEN ASET PADA PT. NATURAL PERSADA MANDIRI BERBASIS WEBSITE - Dimas Arya Senja Raharja; Mahmudin; Asep Abdul Sofyan (Universitas Islam Syekh Yusuf Tangerang, 2026)
The development of information technology allows businesses to improve the efficiency of digital asset management. The purpose of this study is to develop and implement an asset management application that can be accessed through the website at PT. Natural Persada Mandiri to facilitate centralized recording, monitoring, and reporting of company assets. The system development method used is Extreme Programming, starting from Planning, Design, Coding to Testing. Two methods are used to conduct system testing, namely Black Box testing which evaluates the functionality of each aspect of the application, and User Acceptance Testing (UAT), which measures the level of user satisfaction with the system being developed. Black Box testing revealed that all features functioned well without any problems. Meanwhile, the results of User Acceptance Testing (UAT) showed a satisfaction level of 81.8%, indicating that users welcomed the system and effectively met business needs. Researchers solved the problems that existed at PT. Natural Persada Mandiri, which still used Google Spreadsheet as a system for its asset processing. Where there were errors in input, output, and human error. Researchers created an asset management system using PHP and Laravel technology.